Improved Embryo Transfer into the Oviduct by Local Application of a Vasoconstrictor in Mice - SUZUKI, Hiroshi; SHINO, Masao; KAMADA, Nobuo; JISHAGE, Kouichi; UEDA, Otoya; KATOH, Motoe (Journal of Mammalian Ova Research, 1994)
Embryo transfer into the oviduct was improved by local application of a vasoconstrictor. Conventional embryo transfer into the oviduct (Conventional method), embryo transfer through the oviducal wall (Nakagata method) and embryo transfer into the oviduct by means of a vasoconstrictor (Vasocontriction method) were compared by two technicians. In the Conventional method, the bursa over the infundibulum has a hole torn in it with watchmaker's forcepts, In the Nakagata method, the oviducal wall is cut with a fine scissors and a pipette inserted into the oviduct. In the Vasoconstriction method, several microlitters of the epinephrin solution (Bosmin) are applied onto the surface of the bursa before tearing a hole in it. Developmental rates after embryo transfer were not significantly different among three methods. By means of the vasoconstrictor, however, the percentage of time taken for introducing embryos was significantly reduced. Although results of postimplantation development after transfer tended to show that the Vasoconstriction method was more successful than those of the other methods, these differences were not significant. Development rates to newborns indicate that the application of a vasoconstrictor to the bursa does not affect the maintenance of pregnancy.